Pentingnya Peran Orang Tua Dalam Pendidikan Karakter Anak - Syifa Salma (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
The task of parents is to provide proper education to their children from an early age until adulthood. Education: A child's personality and individuality should be formed first in the family environment. Parents must have concepts and rules in raising children, including moral and ethical education, religious knowledge education, fair treatment of children, as well as good care and love for each child. Parents are role models for their children. Therefore, the role of parents in forming character and personality during a child's growth period is very important. The aim of this research is to clarify the role and development of children's personalities.